Pemberdayaan Masyarakat Desa Dalam Pemanfaatan Sampah Organik Melalui Pelatihan Pembuatan Pupuk Organik - Syaifudin, Andang; Avitasari, Ratna; Lestari, Yunita Dwi; Lutfi, Jihan; Maula, Indah Safaatul; Mauludi, Ahmad; Karnila, Karnila; Nadhiroh, Ayu Lailatun; Sari, Septina Putri Nur Wulan; Astuti, Fitri Puji (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Soil conditions vary from region to region. Some are fertile, while others are less fertile. Factors such as nutrient imbalance, soil depletion, decreased organic content, and microbial activity affect soil fertility. To maintain the balance of soil nutrients and organic matter, it is necessary to add organic fertilizers to harmonize the nutrient content of the soil. Chemical fertilizers only provide one type of plant nutrient without improving soil properties. Socialization of organic fertilizers is needed so that people are wiser in maintaining soil fertility with organic materials. The community service was carried out to provide training and practice in making organic fertilizer from livestock manure and plant residues in Duku Candi Baru, Genting Village, Cepogo District, Boyolali Regency. This service activity uses two approaches, namely counseling and training. The extension stage is carried out by providing material about processing cow dung into organic fertilizer. Training is carried out by demonstrating how to make organic fertilizer in a simple way. This training begins with the socialization of making organic fertilizer and compost, which aims to make the community understand first about information about organic fertilizer and compost along with its benefits, then continued with the practice of making organic fertilizer and compost. This training educates the community about the use of organic waste for organic fertilizer in sustainable agriculture. Through a mixture of simple materials such as cow dung, vegetable waste, EM4, and molasses, it is hoped that the community will use organic fertilizers rather than chemical fertilizers for more environmentally friendly agricultural products.